Communication Strategy in Attracting Public Interest - Asmaul Hasanah (Yayasan Avicenna, 2023)
The purpose of this research is to identify communication strategies that are more effective in attracting people's interest in joining the madrasa and their obstacles. This research uses a qualitative approach and case studies to understand the communication strategy at madrasa based on pesantren and its impact on public interest. Data was collected through interviews with various related parties, participatory observation, and document analysis. The results of the research will provide insight into effective communication strategies in Islamic boarding schools and the level of community involvement in the institution's activities. The results of this work are a). Through an effective communication strategy, the madrasa has succeeded in increasing public interest in their education program, by identifying audiences, crafting convincing messages, and utilizing various media to reach a wider audience. The madrasa based on pesantren is an effective agent of change in awakening and fostering rural communities. b). The madrasa based on pesantren faces constraints of limited resources and a lack of communication skills in implementing communication strategies, but by utilizing local resources, skills training, and curriculum innovation, they have the potential to become more effective agents of change in attracting the interest of rural communities.